Analisis Penggunaan Media Sosial Dan Sumber Belajar Digital Dalam Pembelajaran Bagi Siswa Digital Native Di SMAN 2 Painan - Sona Rahmada Yani; Menik Kurnia Siwi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2020)
The purpose of this study is to find the effect of the use of social media and digital learning resources fordigital native in learning. Type of this research is associative descriptive. Descriptive research is research that describes or explains something of the relationships and influences between variables as they are. While associative research is research looking for relationships between a variable with other variables. The population of this study was Class XI IPS 1, XI IPS 2 and XI IPS 3 in SMAN 2 Painan. The sample used in this study was obtained by total sampling of 97 people. Based on the results of research and discussion on the use of social media it can be concluded that the use of social media by digital native students at SMAN 2 Painan can be classified as quite high. And the use of digital learning resources by native digital students can be classified as quite high. This means that digital learning resources have a positive impact if used continuously in learning. DOI: https://dx.doi.org/10.17977/um014v13i12020p001